Голлистские принципы внешней политики в трaнсрегионaльных реaлиях периодa после «холодной войны» - Baizakova, K.; Chabal, P. (International relations and international law Journal, 2018)
This article is dedicated to study one of the aspects of Charles de Gaulle`s legacy, the first President of the Fifth Republic in France, namely to his principles in foreign policy. How relevant are these principles today, in the conditions of the post cold war international relations? Key in concept of French diplomacy are terms of national independence. Whole General de Gaulle`s activity in period of exile, and in the period of presidency was devoted to general aim – to achieve true national independence of France in the international level. Official position and the concept of Gaullism in the issue of European integration was also subordinated to the task to preserve the independence of member states of the European Community. On the other hand, namely Charles de Gaulle advocated the principles of multilateralism. Despite the change of geopolitical situation after the end of the cold war, France retains basic principles of its own foreign policy founded by S. de Gaulle. The essence of these principles – preservation of national independence of France in the name of its national interests. Key words: Gaullism, French foreign policy, interregional cooperation, multilateralism, national interests.